2012
DOI: 10.1155/2012/198453
|View full text |Cite
|
Sign up to set email alerts
|

Magnetostatic Interaction in Fe‐Co Nanowires

Abstract: Arrays of Fe-Co alloy nanowires with diameter around 35 nm and several micrometers in length have been synthesized by codepositing Fe and Co into porous anodic alumina. The morphology, structure, and magnetic properties of the nanowires (hysteresis loops and remanence curves) were characterized by SEM, TEM, X-ray diffraction (XRD), and VSM, respectively. The XRD patterns indicate that the Fe-Co nanowires present a body-centered cubic (bcc) structure and a preferred (110) orientation perpendicular to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 25 publications
1
18
0
2
Order By: Relevance
“…12. The coercivity exhibited a linear decrease with the increasing of length and diameters, which is generally observed for ferromagnetic materials experimentally, 24,41,[52][53][54] indicating that the shape anisotropy dominates the total effective anisotropy.…”
Section: D20supporting
confidence: 60%
See 2 more Smart Citations
“…12. The coercivity exhibited a linear decrease with the increasing of length and diameters, which is generally observed for ferromagnetic materials experimentally, 24,41,[52][53][54] indicating that the shape anisotropy dominates the total effective anisotropy.…”
Section: D20supporting
confidence: 60%
“…Similar behavior, as a function of wires dimensions, was observed for other CoFe nanowire arrays. [15][16][17][18][19][20][21][22][23][24][25][26][27] …”
Section: Controlled Electrodeposition Of Comentioning
confidence: 99%
See 1 more Smart Citation
“…Varieties of FeCo alloy nanowires can be prepared by electrodeposition using the porous alumina membranes as templates [19][20][21]. The liquid-phase chemical reduction is another method often used to synthesize Fe-based nanoparticles [22,23].…”
Section: Introductionmentioning
confidence: 99%
“…An AC (alternative current) current condition was used, 200 Hz and a cell potential of 15 V (AC). Elbaile et al [109] reported pulse deposition to fabricate Fe-Co alloys. Compared to galvanostatic and potentiostatic deposition, pulse deposition was more beneficial to control the length and uniformity of nanowires.…”
Section: Co-ni Co-fe Nanowiresmentioning
confidence: 99%